1968
DOI: 10.1084/jem.128.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Intestinal Microvillous Membranes

Abstract: Antibodies (AbMVM) were produced in rabbits to microvillous membranes isolated from hamster small bowel. Incubation of frozen sections of hamster small bowel with fluorescein-labeled AbMVM showed specific reaction with brush borders, but not with other intestinal cellular components. Electron microscopy with ferritin-conjugated AbMVM localized the antigens more precisely to the surface mucopolysaccharide coat of the brush borders. AbMVM also reacted with the brush border of colon and of proximal renal tubules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
1987
1987

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The present schema for vitamin B1n absorption envisages the ingestion of vitamin B12 (actually coenzyme B12 bound to protein [10][11][12][13]), release from its protein bond as a result of proteolytic digestion in an acid medium, binding to intrinsic factor in the stomach or upper portion of the small bowel (14)(15)(16), passage down the small bowel, attachment of the IF-B12 complex to a specific receptor located in the brush border of the ileal epithelial cell (17)(18)(19)(20)(21), and eventual release of the vitamin into the portal circulation unaccompanied by IF (22,23). In addition a factor elaborated by the pancreas may be an obligatory requirement for optimal vitamin Bi2 absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The present schema for vitamin B1n absorption envisages the ingestion of vitamin B12 (actually coenzyme B12 bound to protein [10][11][12][13]), release from its protein bond as a result of proteolytic digestion in an acid medium, binding to intrinsic factor in the stomach or upper portion of the small bowel (14)(15)(16), passage down the small bowel, attachment of the IF-B12 complex to a specific receptor located in the brush border of the ileal epithelial cell (17)(18)(19)(20)(21), and eventual release of the vitamin into the portal circulation unaccompanied by IF (22,23). In addition a factor elaborated by the pancreas may be an obligatory requirement for optimal vitamin Bi2 absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal tissue segments approx. 0.5 cm in length were fixed in 10% (v/v) neutral buffered formalin for 4 h at room temperature and left in 30% (w/v) sucrose in water overnight at 4°C (Kopp et al, 1968). The segments were embedded in O.C.T.…”
Section: Immunoffuorescent Localizationmentioning
confidence: 99%
“…Many short-term experiments (2 hr or less) have been satisfactorily conducted by maintaining open intestinal segments or everted rings and sacs of intestinal tissue in suitable oxygenated buffer solutions (1,2). Careful morphological studies have shown that epithelial cell integrity is maintained in these short-term experiments (3)(4)(5). However, marked epithelial cell necrosis and disintegration occurs if incubation of intestinal tissue is prolonged much beyond 2 or 3 hr.…”
Section: Introductionmentioning
confidence: 99%